Leadhership and Team work On Employee Performance Pada Bank BRI KCP Unit Blimbing Malang - Yuyuk Liana; M. Ridlo Arifki; Ali Lating; Taufik Djafri (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This study aims to analyze the influence of leadership and teamwork on employee performance. The population in this study is Bank BRI KCP Unit Blimbing Malang, which operates in the banking sector. The samples were taken using a random sampling technique, with a total of 32 respondents, the data analysis technique used is multiple linear regression analysis with SPSS. The results of this study indicate that the leadership variable affects employee performance and the teamwork variable affects employee performance.